MENERAPKAN MANAJEMEN PERUBAHAN DAN MENGHADAPI PERSAINGAN ERA SOCIETY 5.0 DALAM PT. UNILEVER - Nabila Alodia; Jumawan, Hadita, Karina Rachmawati, Bunga Nur Kaunaini, Enjelya Peronika Lumban Toruan, Prayuda Putr (Adisam Publisher, 2023)
The era of Society 5.0 brought great changes in human life around the world. This change is marked by the rapid introduction of information and communication technology aflecting many aspects of people's lives, including the way we work and the way we work, interact to what we buy. In this research method, the author uses qualitative research strategies in evaluating journal literature. The chain of events method uses legitimate journals, e-books, medical books, and websites. The data collected in the study will then be interpreted a series of notes by downloading newspapers published on Google Schooler and legitimate news sites. In anticipation of changes in shopping patterns that are now completely online, Unilever Indonesia has given birth to many innovations in the digital field such as: Unilever Home Delivery, an increasingly strong presence in the e-commerce channel, services to answer consumer needs at a professional level through Unilever Professional, and the launch of the Sahabat Warung application to help stall merchant partners to stay healthy, safe and able to continue selling. In this context, eflective leadership is the key to success in managing the change process.